Boson Sampling from a Gaussian State - Lund, A. P.; Laing, A.; Rahimi-Keshari, S.; Rudolph, T.; O’Brien, J. L.; Ralph, T. C. (Physical review letters, 2014)
We pose a randomized boson-sampling problem. Strong evidence exists that such a problem becomes intractable on a classical computer as a function of the number of bosons. We describe a quantum optical processor that can solve this problem efficiently based on a Gaussian input state, a linear optical network, and nonadaptive photon counting measurements. All the elements required to build such a processor currently exist. The demonstration of such a device would provide empirical evidence that quantum computers can, indeed, outperform classical computers and could lead to applications.